Analisis Kemampuan Pemahaman Konsep Matematika Siswa SMK RPI Jakarta pada Materi Matriks - Yogi Arif Fathan (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Education is a learning process aimed at developing individual potential in cognitive, affective, and psychomotor aspects, enabling them to contribute optimally to society. In formal education, such as in schools, various disciplines are taught, including mathematics, which helps students think logically, analytically, and solve problems. Mathematics education is expected to help students understand concepts that can be applied in various fields of science and real-life situations. Students should understand mathematical concepts, recognize relationships between concepts, derive formulas and properties, perform mathematical operations for generalization, gather evidence or explain ideas and mathematical statements, solve problems, use mathematics to communicate ideas, explain situations or problems, and appreciate the importance of mathematics in their lives. Conceptual understanding represents the lowest level of the cognitive domain and is a crucial learning objective as it provides the understanding that the lessons taught are not merely about mathematics. The conceptual understanding of mathematics among the 24 students in class XI at SMK RPI Jakarta resulted in an average score of 76.9. This indicates that the majority of students have a good understanding of the concepts, although some still require improvement..